Pengaruh Model Pembelajaran Penemuan dan Motivasi Belajar Terhadap Hasil Belajar Fisika - Siti Hajar; Kaharuddin Arafah; Muhammad Sidin Ali (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2020)
Abstract - The purpose of this study was to analyze the differences in physics learning outcomes between students taught using the discovery model and problem solving models, both overall, high learning motivation, and low motivation to learn. In addition, to analyze the effect of interactions between learning models with learning motivation on student physics learning outcomes. To achieve these objectives, an experimental study using treatment by level design, 2 x 2 factorial. The population of this study were all students of grade XI MIA SMAN 9 Makassar. The research sample subjects were taken through cluster random sampling technique. Grade XI MIA 1 and MIA 3 students as an experimental class taught using the discovery model. While students of grade XI MIA 2 and XI MIA 4 as controls are taught using problem solving models. Data collection about physics learning outcomes and learning motivation using test and non-test instrument techniques. Data were then analyzed using two-way ANOVA. The results showed that overall, there were differences in physics learning outcomes between students who were taught using the discovery model and problem solving models. Furthermore, there is no effect of interaction between learning models with learning motivation on learning outcomes in physics. There is a difference in physics learning outcomes between students taught using the discovery learning model and problem solving models, both students who have high motivation to learn and those who have low learning motivation.Keywords: discovery model, problem solving, learning motivation, treatment by level design, two-way ANOVA, physics learning outcomes.